Navigational, Historical and Environmental Perspective of Jupiter Inlet and the Loxahatchee River - David A. Fann; Robert A. Swett; Michael J. Grella (EDIS)
SGEB-57, a 2-page full-color map by David A. Fann, Robert A. Swett, and Michael J. Grella, uses natural-color aerial photographs along with historic pictures and maps to help visitors and residents enjoy and appreciate what they can see and access from recreational vessels in the Jupiter Inlet vicinity. Published by the Florida Sea Grant Program, March 2006.